A System For Interactive Error Detection - Wilson, G.A.; Salazar, S.B. (Fifth International Conference on Very Large Data Bases, 1979, 1979)
The system described in part in this paper is one of the ongoing research efforts to provide powerful automated tools for coping with data base error detection. Intended as a 'filter' between the users and their DBMS, the Cooperative Overt Passive Error-Detection (COPE) system is designed to be easily interfaced to virtually any DBMS. COPE makes a clear distinction between the knowledge required to detect data base errors, and the procedures needed to apply that knowledge, The knowledge is represented in a DBMS independent Conceptual Model in the form of a special purpose language. This paper describes the mechanisms employed in COPE to apply the error detection knowledge of the Conceptual Model. The concept of dynamic transactions, transactions constructed on-the-fly, is introduced. Dynamic transactions permit the system to create independent user contexts, which are single user views of a data base in the process of being updated. In addition to checking for errors within each user's actions, the system avoids having errors introduced in the data base due to undesirable interactions between users. The use of these techniques enables COPE to be applied to both pre-existing data bases, and proposed data base updates. The system can operate interactively, so that users may request explanations for the errors reported to them, and obtain some forms of assistance in determining appropriate corrections.